2010
DOI: 10.1364/oe.18.000780
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal heterodyne holography of gold nanoparticles

Abstract: We report a method based on heterodyne numerical holography associated to photothermal excitation for full field and three-dimensional localisation of metallic nanoparticles. A modulated pump laser (lambda = 532 nm) heats several particles, creating local refractive index changes. This modulation is detected using a probe and a local oscillator beam (lambda = 785 nm), frequency-shifted to create a hologram beating at low frequency. Tens of particles, down to diameters of 10 nm, can be localised simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 11 publications
(19 reference statements)
4
54
0
Order By: Relevance
“…The linear increase of the SNR with the integration time, the probe power and with the square of the heating power was confirmed experimentally. This is consistent with previous studies [7,12,20,23].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The linear increase of the SNR with the integration time, the probe power and with the square of the heating power was confirmed experimentally. This is consistent with previous studies [7,12,20,23].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, only highly concentrated solutions of relatively large nanoparticles (30 to 120 nm) provided detectable signals. Another interesting approach based on digital holography reported on the heterodyne detection of single gold particles down to a diameter of 10 nm [23]. However, the photothermal signal arose only in a small sub-area of the available field of view (FOV) and although depth sectioning was demonstrated, no three-dimensional localization of AuNPs was shown.…”
Section: Introductionmentioning
confidence: 99%
“…The reconstruction of the hologram is achieved numerically after kspace filtering using a method inspired by Cuche et al [27]. The off-axis configuration, combined with heterodyne modulation, allows spatial and temporal filtering, yielding excellent signal-to-noise ratios and sensitivities [25,28].…”
Section: Methodsmentioning
confidence: 99%
“…While this approach showed the potential of the combination of photothermal excitation and digital holography, the evanescent field excitation limited the amount of information that could be recovered about the rest of the sample, such as the presence and structure of cells. A more detailed study from this group [47] characterized the approach in more detailed and identified that using larger particles enabled improvement of SNR to 90 and again confirmed the 90dB potential SNR when coherent noise could be avoided. This latter study identified that this approach would trail single particle photothermal interferometry by an order of magnitude or greater in SNR and that the need for a widely distributed reference field might cause sample damage when imaging cells.…”
Section: Digital Holographymentioning
confidence: 72%